Analysis of Marketing Strategies For Health Services in The National Health Insurance Era in Hospital Muhammadiyah Bandung - Sahya Muspita; Ai Susi Susanti (Asian Journal of Environmental Research, 2024)
The National Health Insurance (JKN) has brought significant changes to the healthcare industry. The programme provides financial protection to Indonesians to meet their basic health needs. In the JKN era, hospitals are also faced with challenges and intense competition, so they need to improve service quality and implement effective marketing strategies. The purpose of this study is to analyse the application of the marketing mix in the marketing strategy implementation process as well as the selected marketing strategy in the JKN era at Muhammadiyah Bandung Hospital. This study used a descriptive research method with a qualitative approach, which involved interviews with the head of the marketing unit and the hospital's marketing executive staff. The results showed that well-targeted marketing strategies can strengthen the hospital's image, increase visibility and public awareness of the hospital's healthcare offerings, thus helping to reach more potential patients, and improve patient satisfaction. The implications of this study emphasise the important role of effective marketing strategies in improving healthcare services at Rumah Sakit Muhammadiyah Bandung in the era of the National Health Insurance (JKN).